2007
DOI: 10.1073/pnas.0705149104
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic interplay between nitration and phosphorylation of tubulin cofactor B in the control of microtubule dynamics

Abstract: Tubulin cofactor B (TCoB) plays an important role in microtubule dynamics by facilitating the dimerization of α- and β-tubulin. Recent evidence suggests that p21-activated kinase 1 (Pak1), a major signaling nodule in eukaryotic cells, phosphorylates TCoB on Ser-65 and Ser-128 and plays an essential role in microtubule regrowth. However, to date, no upstream signaling molecules have been identified to antagonize the functions of TCoB, which might help in maintaining the equilibrium of microtubules. Here, we dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…The highly electronegative orthophosphate group likely would not permit the addition of a nitro group at the meta position of the same tyrosine ring. A balance between nitration and phosphorylation at specific amino acids may have some biological importance, 26,46 but this hypothesis requires further study.…”
Section: Timing Of Nitration During Tangle Evolution In Ad Pathogenesismentioning
confidence: 99%
“…The highly electronegative orthophosphate group likely would not permit the addition of a nitro group at the meta position of the same tyrosine ring. A balance between nitration and phosphorylation at specific amino acids may have some biological importance, 26,46 but this hypothesis requires further study.…”
Section: Timing Of Nitration During Tangle Evolution In Ad Pathogenesismentioning
confidence: 99%
“…Indeed, mutated forms of TBCB at its phosphorylation sites inhibit microtubule regrowth from the centrosome after nocodazole treatment and washout (80). More recently, it has been shown that TBCB, just like tau and a-tubulin, undergoes nitration, which inhibits the polymerization of new microtubules (81). The inhibition of microtubule regrowth in this case seems to be related to the fact that tyrosine nitration of TBCB inhibits its ability to undergo phosphorylation.…”
Section: Centrosomal Microtubule Nucleation and Assembly Depends On Tmentioning
confidence: 97%
“…5 Further, nitration at a tyrosine residue can modulate phosphorylation of neighboring sites. 20 To examine the potential effect of nitration on signaling pathways, we first collected phosphorylation sites for the 23 NPs from the following three PTM databases (Phosphosite Plus, 29 Phosida, 30 Phospho.ELM…”
Section: Uniprotmentioning
confidence: 99%
“…PTN exerts its functions by modulating phosphorylation of the nitrated tyrosine or neighboring serine/threonine residues. 20 Thus, the comparison between the detected nitrated and known phosphorylation sites can reveal functional implication of the nitrated sites. •) is necessarily needed to initiate this modification.…”
mentioning
confidence: 99%